2016
DOI: 10.1007/s11695-016-2111-6
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Metabolic Factor Before and After Bariatric Surgery

Abstract: This study seems to establish the possibility that metabolic factor is not simply a function of one's current weight, but instead might be a stable characteristic unique to each individual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…We acknowledge that these findings seem contradictory. However, it should be noted that weight loss in general is associated with metabolic slowing exemplified by decrease in resting metabolic rate . Slowing of the metabolism results in slower weight loss and a risk of weight regain .…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that these findings seem contradictory. However, it should be noted that weight loss in general is associated with metabolic slowing exemplified by decrease in resting metabolic rate . Slowing of the metabolism results in slower weight loss and a risk of weight regain .…”
Section: Discussionmentioning
confidence: 99%
“…than normal weight people, but measurement has been difficult 8-10. A study by Davis and Indelicato 11 demonstrated that even with massive postsurgical weight loss, obese people did not have significant changes in Metabolic Factor. The initial weight for the 18 participants was 326.3 pounds (91.3).…”
mentioning
confidence: 99%
“…The mechanism of action likely involves stimulation of gastric mechanoreceptors triggering short-acting vagal signals to brain regions implicated in satiety [5]. Resting metabolic rate (RMR) is elevated among obese individuals; compared with healthyweight individuals it was shown to decrease with weight loss induced by dietary and/or physical activity interventions [6][7][8][9][10][11][12]. However, increases in RMR of individual patients were reported [13].…”
mentioning
confidence: 99%
“…However, increases in RMR of individual patients were reported [13]. RMR divided by current weight (RMR/mass) [10,14] is lower among obese individuals, compared with individuals who are overweight or at normal weight [12]. After diet-restriction therapies accompanied by vigorous physical exercise, RMR/mass was reported to decrease [9] or increase (in an extreme case of 35% loss of initial weight) [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation